2018
DOI: 10.1002/jcb.27837
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine stimulates IL‐6 expression by activating the AP‐1 and STAT‐3 pathways in human endothelial EA.hy926 cells

Abstract: Interleukin‐6 (IL‐6), a pleiotropic cytokine, plays a key role in endothelial injury and atherosclerosis. In this study, we investigated the effects of nicotine, a major psychoactive compound in cigarette smoke, on IL‐6 expression and EA.hy926 endothelial cell invasion. Nicotine stimulated IL‐6 expression via the activator protein 1 (AP‐1) transcription factor. Pharmacological inhibition and mutagenesis studies indicated that p38 mitogen‐activated protein kinase (MAPK) mediated the IL‐6‐induced upregulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Indeed, IgG4-RD RI, rather than serum IgG4, is closely related to disease activity (23,38), indicating that the increased level of IL-6 was directly correlated with disease activity and was also involved in the development of IgG4-RD. As a critical pro-inflammatory factor, IL-6 is produced by both immune cells, as well as various types of tissue cells (e.g., fibroblasts, epithelial cells, and keratinocytes) under the stimulation of IL-1, TNF-α, PDGF, virus, doublestranded RNA, and c-AMP, and subsequently promotes the development of inflammatory and autoimmune diseases (54)(55)(56)(57)(58). However, whether tissue cells in the affected organs of IgG4-RD can produce IL-6 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, IgG4-RD RI, rather than serum IgG4, is closely related to disease activity (23,38), indicating that the increased level of IL-6 was directly correlated with disease activity and was also involved in the development of IgG4-RD. As a critical pro-inflammatory factor, IL-6 is produced by both immune cells, as well as various types of tissue cells (e.g., fibroblasts, epithelial cells, and keratinocytes) under the stimulation of IL-1, TNF-α, PDGF, virus, doublestranded RNA, and c-AMP, and subsequently promotes the development of inflammatory and autoimmune diseases (54)(55)(56)(57)(58). However, whether tissue cells in the affected organs of IgG4-RD can produce IL-6 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As a critical pro-inflammatory factor, IL-6 is produced by both immune cells, as well as various types of tissue cells (e.g., fibroblasts, epithelial cells, and keratinocytes) under the stimulation of IL-1, TNF-α, PDGF, virus, double-stranded RNA, and c-AMP, and subsequently promotes the development of inflammatory and autoimmune diseases ( 54 58 ). However, whether tissue cells in the affected organs of IgG4-RD can produce IL-6 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis and diabetes have raised pro‐inflammatory cytokine levels, comprising TNF‐α, interferon‐γ (INF‐γ), IL‐1β, IL‐6, and interleukin‐17 (IL‐17) 25,26 . IL‐6 has been the most investigated among them and could involve in endothelial dysfunction by stimulating adhesion molecule and cytokine levels, migration, and adhesion in vascular smooth muscle cells and endothelium 27–29 . From this, it is found that IL‐6 and VCAM‐1 were upregulated in vascular walls in diabetes with periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“… 52–54 On the other hand, nicotine stimulates increased expression of IL-6 through the p-38 MAPK/AP-1 and ROS/STAT-3 signalling pathways that trigger endothelial injury. 15 , 55 …”
Section: Discussionmentioning
confidence: 99%